2021
DOI: 10.3390/cancers13081781
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Application of Monoclonal Antibodies in Pancreatic Cancer: Advances, Challenges and Future Opportunities

Abstract: Pancreatic cancer remains as one of the most aggressive cancer types. In the absence of reliable biomarkers for its early detection and more effective therapeutic interventions, pancreatic cancer is projected to become the second leading cause of cancer death in the Western world in the next decade. Therefore, it is essential to discover novel therapeutic targets and to develop more effective and pancreatic cancer-specific therapeutic agents. To date, 45 monoclonal antibodies (mAbs) have been approved for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 217 publications
(239 reference statements)
0
16
0
Order By: Relevance
“…Pancreatic cancer is one of the deadliest human cancers [1] and has a very poor 5-year survival rate [2]. Studies have shown that smoking, alcohol consumption, dietary factors, diabetes, obesity, and genetics are important factors associated with the incidence of pancreatic cancer [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic cancer is one of the deadliest human cancers [1] and has a very poor 5-year survival rate [2]. Studies have shown that smoking, alcohol consumption, dietary factors, diabetes, obesity, and genetics are important factors associated with the incidence of pancreatic cancer [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Antibody arrays, which have been variously developed for biomarker detection in pancreatic cancer [ 36 , 37 ], might be applied in the 64 Cu-TuBA format in the future. Thus far, no pancreatic cancer-specific therapeutic antibodies have been approved for the treatment of pancreatic cancer despite the effort of previous studies; that is, it is difficult to cover most pancreatic cancer patients by targeting one specific target antibody [ 38 ]. Therefore, personalized 64 Cu-ipRIT with 64 Cu-TuBA could be a beneficial strategy for pancreatic cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Pembrolizumab can bind to PD-1, antagonize PD-1 interaction with its ligands, and enable the immune system to eliminate cancer cells ( Sahni et al, 2018 ). The first tissue-agnostic/site-agnostic medication, pembrolizumab is effective for treating melanoma, NSCLC, recurrent or metastatic cervical cancer, metastatic SCLC, endometrial carcinoma, TMB-H solid tumors, MSI-H or dMMR CRC, triple-negative breast cancer expressing PD-L1 and other types of cancer ( Arias-Pinilla and Modjtahedi 2021 ). In addition, the NCCN guidelines state pembrolizumab can be considered a second-line or subsequent treatment for cervical malignancies that are PD-L1 positive, MSI-H/dMMR, and TMB-H recurrent or metastatic ( NCCN Guidelines 2022 ).…”
Section: Monotherapy With Pd-1/pd-l1 Inhibitorsmentioning
confidence: 99%